ANALYSIS OF FACTORS RELATED TO NURSES RESILIENCE IN THE INPATIENT ROOM ST. CAROLUS HOSPITAL, JAKARTA - Utami, Lucia; Tarapanjang, Antonius (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2024)
Background: Nurses are one of the professions that have high levels of stress. Many situations put nurses are exposed to a variety of severe occupational stressors such as a high workload, time pressure, working conditions, shift work, and low social support at work. Therefore nursing staff need to have adequate resilience. Resilience is an ability possessed by individuals and with this ability individuals are able to survive and develop healthily and live life positively in unfavorable and positively in unfavorable and stressful situations pressure. Spirituality, self-efficacy, and optimism can affect the resilience of nurses. Resilience possessed by nurses will help nurses deal with difficulties or failures that can lead to anxiety and depression. Objective: To determine the relationship between spirituality, self-efficacy, and optimism with nurse resilience in the inpatient ward. Methods: Quantitative descriptive correlation cross sectional design, conducted from January - May 2023 at St. Carolus Hospital Jakarta. The sample totaled 90 nurses in the inpatient ward using purposive sampling technique. Bivariate data was analyzed using Kendall's Tau C and multivariate data was analyzed using Logistic Regression. Results: there is a significant relationship between resilience and spirituality (p value = 0.005). There is a significant relationship between resilience and optimism (p value = 0.001). There is no significant relationship between resilience and self-efficacy (p value = 0.077). Regression test results show that there is no factor that is most related to resilience. Conclusion: There is a significant relationship between resilience with spirituality and optimism. However, there is no relationship between resilience and self-efficacy. It is concluded that there is no factor that is most related to the resilience of nurses in the inpatient ward of St. Carolus Hospital Jakarta in 2023.